The current status and future prospects of artificial intelligence education in residency training - Zhang, Hongsen; Qian, Kun; Wang, Jing; Zheng, Chuansheng (Frontiers in Education, 2026)
With the rapid advancement of artificial intelligence (AI) technology, its applications in medicine have grown increasingly widespread. In particular, AI has shown significant potential within residency education. This review examines current uses of AI in residency training, focusing on innovative educational models, curriculum design, outcome assessment, and existing challenges. By analyzing recent research across medical specialties, the discussion explores the role of AI in personalized learning, examination assistance, and clinical decision support. Furthermore, future strategies for integrating AI into residency education are proposed. This article aims to provide a comprehensive theoretical and practical reference for medical educators and policymakers, supporting the scientific application and continued development of AI in residency training.